A Multiscale Approach to Identifying Vernacular Landscape Pattern Characteristics in River Basins: A Case Study of the Liuxi River, Guangzhou - Nanxi Wang; Yan Zha; Zhongxiao Lin (Land)
In recent years, rapid urbanization has transformed the man–land relationship in rural areas, highlighting issues such as the homogenization of vernacular landscapes. This study uses the Liuxi River in Guangzhou as a case and applies a hierarchical interpretation system for vernacular landscapes, utilizing methods from landscape character assessment (LCA) and Historic Landscape Characterization (HLC). Focusing on two scales, “basin” and “vernacular unit”, this study proposes a framework for identifying vernacular landscape patterns. This framework includes scale definition, pattern identification, feature description, and factor analysis. At the basin scale, the investigation concentrates on spatial configurations of vernacular landscapes in 1985, whereas the unit-scale analysis delineates temporal evolutionary trajectories spanning 1974–2020. The results indicate significant differences in landscape fragmentation, dominance, and diversity between upstream and downstream at the basin scale. At the unit scale, the landscape connectivity in the Shaxi River unit remains relatively stable, while landscape heterogeneity increases, resulting in greater diversity. This study provides valuable insights into the continuity and development of diversity in analogous vernacular landscape regions globally, particularly those comparable to the Liuxi River basin.